City of the Undead : Voodoo, Ghosts, and Vampires of New Orleans - Roberts, Robin, 1957- (Book collections on Project MUSE., 2023)
"From its looming above-ground cemeteries to the ghosts believed to haunt its stately homes, New Orleans is a city deeply entwined with death, the undead, and the supernatural. City of the Undead explains how the Big Easy came to be synonymous with the paranormal in the form of ghosts, vampires, and Voodoo Queens. The reasons behind New Orleans's reputation as America's most haunted city are numerous. Its location at the mouth of the Mississippi River grants it a liminal status between water and land, while its stately oaks and Spanish moss create an eerie beauty. The ever-mixing blend of spiritual beliefs from Native American, African, African American, Caribbean, and European cultures resulted in a unique ferment of the paranormal. Elaborate cemeteries and ornate architecture, an extremely high death rate in the eighteenth and nineteenth centuries, and a long history of enslavement and oppression laid the groundwork for a cultural scene friendly to stories of Voodoo, ghosts, and vampires. Robin Roberts explores representations of three specific supernatural figures: the Voodoo Queen, the ghost, and the vampire. Reviewing the historical bases for these figures, she examines nonfiction, fiction, TV and film, and walking tours to discover how stories of the supernatural can bring attention to the injustices that have faced, and continue to face, marginalized groups in the city. City of the Undead shows how these supernatural figures relate to each other, what function they serve in the greater fabric of the city, and why New Orleans developed and continues to cherish its reputation as a site for the supernatural. It's a city that reminds us of the possibility of life after death and assures us that resistance to injustice need not end in the grave"--